Seat belt repositioning and use of vehicle seat cushions is increased among older drivers aged 75 years and older with morbidities. (30th July 2016) - Brown, Julie; Coxon, Kristy; Fong, Cameron; Clarke, Elizabeth; Rogers, Kris; Keay, Lisa
Abstract : Objective: Good seat belt fit and positioning is important for crash protection. Older drivers experience problems in achieving good seat belt fit and often reposition seat belts and/or use seat cushions. Comfort influences these behaviours. This work examines the impact of functional morbidities on belt positioning and accessory use and whether comfort mediates this relationship Methods: Mediation analysis was used to examine the relationship between morbidities affecting physical function, comfort, belt repositions and seat cushion use among 380 drivers aged 75 years and older. Results: Musculoskeletal morbidities increase the likelihood of seat belt repositioning (OR 1.37, 95% CI 1.12–1.67) and comfort partially mediates this relationship ( P = 0.03). Morbidities of any type also increase the likelihood of seat cushion use (OR 1.15 95% CI 1.04–1.27), but comfort plays no role in this relationship ( P = 0.87). Conclusion: Greater awareness among older drivers is needed, to ensure behavioural modifications do not impair their crash protection.